Legenda Andam Dewi Etnik Batak Toba Kajian : Sosiosastra - Simamora, Devina C; Sibarani, Tidora Putri; Halimatussakdiah, Halimatussakdiah (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2024)
Artikel ini mengkaji legenda